Ion Channel Contributions to Morphological Development: Insights From the Role of Kir2.1 in Bone Development - Ozekin, Yunus H.; Isner, Trevor; Bates, Emily A. (Frontiers in Molecular Neuroscience, 2020)
The role of ion channels in neurons and muscles has been well characterized. However, recent work has demonstrated both the presence and necessity of ion channels in diverse cell types for morphological development. For example, mutations that disrupt ion channels give rise to abnormal structural development in species in flies, frogs, fish, mice, and humans. Furthermore, medications and recreational drugs that target ion channels are associated with higher incidence of birth defects in humans. In this review we establish the effects of several teratogens (epilepsy/migraine drugs, nicotine, heat, and cannabinoids) on development. We then propose potential links between these teratogenic agents and ion channels with mechanistic insights from model organisms. Finally, we talk about the role of a particular ion channel, Kir2.1, in the formation and development of bone. Because Ion channels are common targets of many currently used medications, understanding how ion channels impact morphological development will be important for both prevention of birth defects and potentially regenerative medicine. It is becoming increasingly clear that ion channels have functional roles outside of tissues that have been classically considered excitable.